Analysis of work engagement measurement at work from home due to the effect of Covid-19 pandemic - Hujjatullah Fazlurrahman,; Dewie Tri Wijayati,; Hafid Kholidi Hadi,; Zainur Rahman,; Dwiarko Nugrohoseno,; Muhammad Fajar Wahyudi Rahman, (Technium Social Sciences Journal, 2020)
The first research objective is to examine and analyze the effect of flexible work arrangements (FWA) on lecturer work involvement. The second one is to test and analyze the influence of social media on lecturer work involvement. The third one is to test and analyze the effect of self-efficacy on job involvement. The population in this research was those who work at home during a pandemic. The sample size in this study was 55 samples. The analysis technique used Partial Least Square (PLS). The results of this study was that Flexible work arrangements have no effect on employee work engagement. Social media have no effect on employee work engagement. Self-efficacy has a positive effect on employee work engagement. Employee work life balance has a positive effect on employee work engagement. Self-efficacy does not affect work engagement through the level of work life balance of employees. The limitation in this research is that employees work for home because of the pandemic and they live in Indonesia.